Thyroid Hormonal Status in Newly Diagnosed Type 2 Diabetes Mellitus (Bangladesh Journal of Nuclear Medicine, 2018)
Objectives: Diabetes mellitus and thyroid dysfunction are the two most common endocrinopathies seen in general population. The study was done to determine whether there is any co-occurence of thyroid hormonal status alternating in newly diagnosed type 2 diabetes mellitus.Patients and Methods: This Cross-sectional study which was carried out at National Institute of Nuclear Medicine and Allied Sciences and outpatient Department (OPD) of Endocrinology of Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka during the period January 2015 to July 2016. A total of 98 newly diagnosed type 2 diabetic patients (Group I) and 98 healthy individuals (Group II) were enrolled in this study purposively. After taking written consent, history of the study subjects was taken and clinical checkup was done. Age of the subjects of both the group were 30 years and above. Glycemic status of both the group was assessed by measuring fasting blood sugar, blood sugar two hours after 75 gm oral glucose and blood for HbA1C. Patients with type 1 and other form of diabetes mellitus and any condition that may impair glycemic control were excluded from the study. Thyroid hormonal status of both the group was evaluated by measuring patients’ serum TSH by Immunoradiometric Assay (IRMA) and serum FT3 and serum FT4 by Radioimmunoassay (RIA) method in NINMAS. All the data were digitized and analyzed using SPSS – 22.0 software.Results: In this study, mean age of the patients was 46.0 ± 9.7 years and 45.5 ± 7.7 years in group I and group II respectively. Male female ratio was 1:1.45 in group I and 1:1.08 in group II. Fasting blood sugar, blood sugar two hours after 75 gm oral glucose and HbA1c were significantly higher in group I than that of group II. Mean TSH, FT3 and FT4 were 2.37 ± 3.86 mIU/L, 6.35 ± 2.41 pmol/L and 15.79 ± 5.41 pmol/L respectively in group I whereas 2.28 ± 2.67 mIU/L, 6.59 ± 1.83 pmol/L and 16.25 ± 3.46 pmol/L respectively in group II. But there was no statistical significant difference between group I and group II. In group I, sixteen patients had thyroid disorder (seven had hyperthyroidism and nine had hypothyroidism). In group II, five patients had thyroid disorder (two had hyperthyroidism and three had hypothyroidism). The difference was statistically significant. Fasting blood sugar positively correlated with TSH, FT3 and FT4 in group I, similarly HbA1c correlated with TSH and FT4 but not with FT3 in group I.Conclusion: Thyroid disorder was 16.3% in newly diagnosed type 2 diabetic patients and 5.1% in normal individuals.Bangladesh J. Nuclear Med. 20(1): 27-31, January 2017